A mobile extracorporeal extremity salvage system for replantation and transplantation - Kückelhaus, Maximilian; Fischer, Sebastian; Sisk, Geoffroy; Kiwanuka, Harriet; Bueno, Ericka; Dermietzel, Alexander; Alhefzi, Muayyad; Aycart, Mario; Diehm, Yannick; Pomahac, Bohdan (Annals of plastic surgery, 2016)
BackgroundTraumatic amputation is the second leading cause of limb loss in the United States. The preferred treatment is salvage and replantation of the amputated limb, whenever possible, and allotransplantation is a novel procedure whereby healthy limbs are procured from deceased organ donors and t
Gesehen am 02.06.2020